Critical Pedagogy as a Response to Datafication. (October 2019) - Markham, Annette N.
Critical pedagogy is a vital part of building data literacy. It moves beyond the level of data critique to social action in response to datafication. This article contends that academics can do more to teach those in the public sphere as well as classroom to become critical interpretive researchers of their own lived experience, an action/participatory research framework that identifies critical thinking as the purpose of research and improved digital or data literacy as the outcome of research. This article suggests three strategic modes through which the strengths of critical approaches and qualitative epistemologies can be blended to serve as pedagogical tools for understanding and critically analyzing data, datafication, and other aspects of the digital era.